Penyelesaian Sengketa Waris Adat terhadap Tanah Ulayat pada Masyarakat Adat Minangkabau - Satrya Aprilliant Eka Wibawa; Maya Sari Cahya Aisya; Muhammad Panji Lesmana Putra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Amid the development of national law and the increasingly strong influence of Islamic culture in Indonesia, the existence of matrilineal customary law continues to hold an important position and cannot be disregarded in maintaining inheritance systems based on ancestral values. In the matrilineal customary inheritance system, women play a central role as recipients and successors of inherited property because lineage is traced through the maternal line. The Minangkabau community, as one of the ethnic groups that adopts a matrilineal system, possesses distinctive characteristics in preserving the continuity of its customs, culture, and clan identity. One of the essential elements within this system is ulayat land, which serves as the primary asset in customary inheritance. In Minangkabau tradition, ulayat land is classified as harta pusaka tinggi (ancestral inherited property) that carries sacred value; therefore, it is not permitted to be sold because its ownership is communal and passed down from generation to generation within the clan. Nevertheless, the implementation of the Minangkabau customary inheritance system is not free from challenges, one of which is disputes over ulayat land involving different clans claiming rights to the ancestral property. To address such issues, appropriate and effective dispute resolution mechanisms are required. Consequently, this issue constitutes the main focus of this study. This research employs a normative juridical method with a statutory approach. Through this method, the study examines and analyzes judicial considerations as well as the legal consequences arising from the court decision under review. The findings indicate a harmonization between the resolution of ulayat land disputes through judicial institutions and the application of the principles of Minangkabau matrilineal customary law.